Empowering Women Creative Economy Actors in Semarang City Towards Financial Independence - Sundari, Pipit; Hendrayanti, Silvia; Fauziyanti, Wachidah; Estuti, Erni Puji (Society : Jurnal Pengabdian Masyarakat, 2025)
This community service program aims to empower women creative economy actors in Semarang City to increase financial independen. The program is implemented through a participatory approach with the Participatory Action Research (PAR) method, including idenfification of needs, thematic training, intensive mentoring, and joint evaluation. The program targets 25 women micro-entrepreneurs engaged in processes food, handicrafts, and local fashion. The training focuses on increasing managerial capacity and digital marketing skills, such as the use of social media, creating marketplace accounts, financial records, and product packaging. In addition to the technical impact, this activity also fosters self-confidence and a more mature entrepreneurial mindset. Evaluation is carried out through pre-test, post-test and in-depth interviews. This training is able to build networks between pasticipants and show that the active involvement of women in community-based empowerment activities can increase economic independence in a sustainable manner while strengthening the role of women as drivers of the creative economy at the grassroots level.